The influence of bowel management on the frequency of urinary infections in spina bifida patients. Issue 4 (August 2018) - Radojicic, Zoran; Milivojevic, Sasa; Milic, Natasa; Lazovic, Jelena Milin; Lukac, Marija; Sretenovic, Aleksandar
Summary: Objective: To examine the effects of bowel management on the frequency of urinary infections in spina bifida patients. Study design: The research was carried out from 2014 to 2017, with the recruitment process from June 2014 to March 2016. The first group consisted of 35 patients who were administered bowel management combined with anticholinergic medication therapy and clean intermittent catheterization (CIC). The second group consisted of 35 patients who were treated only with anticholinergic medication therapy and CIC. Bowel management included daily enema, laxative application, and a special diet, with a view to treating constipation that was estimated on the basis of Roma III criteria and echosonographically determined transversal rectal diameter. The effects of the administered bowel management on urinary infections were estimated on the basis of the number of urinary infections before and after the administered therapy. The observation period of every patient was 1 year. Results: There were no significant statistical differences regarding age, gender, and baseline clinical features between the two groups. In the group treated with bowel management combined with anticholinergic medication therapy and CIC, the average number of urinary infections was 0.3 ± 0.5 SD, whereas in the group treated exclusively with anticholinergic medication therapy and CIC the average number of urinary infections was 1.1 ± 1.0 SD. There was a statistical difference regarding urinary infections, that is the average number of urinary infections between these two groups of patients ( p  < 0.001). Conclusion: Administering bowel management considerably decreases the frequency of urinary infections, and should form an integral part of treatment of spina bifida patients. Figure Average number of urinary infections in groups with and without bowel management.